(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Marriage is a practice encouraged in Islam as it legalizes the relationship between a man and woman as husband and wife. The implications of the contract of marriage or aqad that has been solemnized is that each of them has rights and responsibilities as prescribed under Islamic law. Islamic law also allows the contracting parties, whether the husband or the wife, to specify other conditions in the marriage contract. Thus, this research aims to discuss the opinions of Islamic jurists on the conditions and provisions of a marriage contract. The discussion also refers to the Islamic Family Law (Federal Territory) Act 1994 on the conditions that can be included in a marriage contract. The content analysis method is used in this research. The findings are that Islamic Law allows women to stipulate certain conditions in the contract of marriage, as as long as these do not contradict the requirements of the aqad and Islam. Keywords: rights, women, conditions, contract, marriage